2015
DOI: 10.1038/ncomms9886
|View full text |Cite
|
Sign up to set email alerts
|

The higher order auditory cortex is involved in the assignment of affective value to sensory stimuli

Abstract: The sensory cortex participates in emotional memory but its role is poorly understood. Here we show that inactivation of the higher order auditory cortex Te2 in rats during early memory consolidation impairs remote first- and second-order fear memories but not the association between two neutral cues. Furthermore, Te2 inactivation prevents changes in the valence of such information. Following the presentation of two auditory cues previously paired with either pleasant or painful stimuli, a large percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
79
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(95 citation statements)
references
References 54 publications
(103 reference statements)
13
79
1
1
Order By: Relevance
“…In support of this notion, we have identified higher order components of sensory cortices, such as the temporal auditory cortex Te2, which are essential for storing remote fearful memories (Cambiaghi et al 2015;Grosso et al 2015b;Sacco and Sacchetti 2010).…”
Section: Introductionmentioning
confidence: 55%
See 4 more Smart Citations
“…In support of this notion, we have identified higher order components of sensory cortices, such as the temporal auditory cortex Te2, which are essential for storing remote fearful memories (Cambiaghi et al 2015;Grosso et al 2015b;Sacco and Sacchetti 2010).…”
Section: Introductionmentioning
confidence: 55%
“…Thus, the auditory cortex may be part of a sensorimotor system that links auditory stimuli to specific motor responses and, therefore, the differences detected in the present study between fear vs. appetitive paradigms may be due to such the different motor responses paired to tones. Because our recent study showed that Te2 activity in the layer II/III is not related to these motor processes 15 (Grosso et al 2015b), it may be that other Te2 layers are recruited by these sensorimotor processes, and specifically the layer V which projects to subcortical structures involved in emotional and motor responses regulation (Paxinos, 2004). To address this issue, we performed zif268 analysis in rats trained to associate an auditory CS to a different motor behaviors, i.e.…”
Section: Te2 Activity After the Recall Of An Auditory Signaled Two-wamentioning
confidence: 99%
See 3 more Smart Citations